The Present Day of Gender Studies in Poland, with Some References to [Past] Croatian Contexts - Kraskowska, Ewa (Poznańskie Studia Slawistyczne, 2016)
The article sums up the anti-gender campaign of 2013–2014 launched in Poland by the Catholic Church and right-wing politicians. The situation is presented with reference to the Croatian „Witches from Rio” case of 1992–1993 in order to demonstrate similarities of the two backlash discourses, both in the choice of rhetorics and topics (e.g. international conspiracy, deviated sexuality, national treason, violation of the natural social order). Finally, the author attempts to diagnose the impact that the campaign has had so far on various gender-focused projects (both in research and teaching) conducted in and outside academia in Poland.